1993
DOI: 10.1007/bf01244934
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic modulation of midbrain dopamine cell firing elicited by stimulation of the locus coeruleus in the rat

Abstract: Electrical stimulation techniques were employed in the chloral hydrate anaesthetized male rat to evaluate if the pontine noradrenergic nucleus locus coeruleus can influence the activity of midbrain dopamine neurons in the ventral tegmental area and zona compacta, substantia nigra. Single-pulse locus coeruleus stimulation evoked an excitation, followed by an inhibition, of the electrical activity of single midbrain dopamine neurons. Neither of these responses were observed in animals pretreated with reserpine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
174
1
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(181 citation statements)
references
References 64 publications
(42 reference statements)
3
174
1
2
Order By: Relevance
“…An enhanced LC firing rate has been shown to potentiate dopaminergic neurotransmission in the ventral tegmental area (VTA)Fnucleus accumbens circuit via a 1 -adrenoceptors in the VTA and accumbens (Grenhoff et al, 1993;Eshel et al, 1990). VTA neurons are also excited by MFB selfstimulation via cholinergic fibers arising in the laterodorsal and pedunculopontine tegmentum (Yeomans et al, 1993;Yeomans and Baptista, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An enhanced LC firing rate has been shown to potentiate dopaminergic neurotransmission in the ventral tegmental area (VTA)Fnucleus accumbens circuit via a 1 -adrenoceptors in the VTA and accumbens (Grenhoff et al, 1993;Eshel et al, 1990). VTA neurons are also excited by MFB selfstimulation via cholinergic fibers arising in the laterodorsal and pedunculopontine tegmentum (Yeomans et al, 1993;Yeomans and Baptista, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The region whose a 1 -receptors have the greatest effect on behavioral activity is the dorsal pons and most likely in the locus coeruleus (LC), which also has one of the highest densities of these receptors in the brainstem (Stone et al, 2004b;Jones et al, 1985). Furthermore, the LC is a site from which self-stimulation can be elicited (Yadin et al, 1983), is highly sensitive to appetitive operant conditioning (Clayton et al, 2004) and has efferent connections with dopaminergic neurons in the ventral tegmental area (Grenhoff et al, 1993;Mejias-Aponte et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, two decades ago it was shown that stimulation of VTA neurons increases the activity of the LC [45]. Similarly, A1, and A2 NE nuclei were shown to provide excitatory stimulation to VTA DA neurons [53, 54]. Further indirect evidence for NE-DA interaction at the level of the VTA has been provided by autoradiographic and immunohistochemical studies, showing alpha1 and alpha2- adrenergic receptor (AR) expression in most DA neurons of the VTA [55, 56].…”
Section: The Anatomy Of Ne-da Interactionsmentioning
confidence: 99%
“…Regarding mesencephalic DA neurons, NE also modulates VTA DA neurons [53, 54, 119] and there is evidence that NE-containing axons directly project to the VTA and NAc. Thus, it is likely that NE is important for ventral striatal DA release as well.…”
Section: The Role Of Ne In Methamphetamine-induced Behavioural Changesmentioning
confidence: 99%
“…It is currently thought that the a 1 -receptors involved in motor activity exert this function in large part via modulatory effects on dopaminergic neuronal firing rate (Berretta et al, 2000;Grenhoff et al, 1993Grenhoff et al, , 1995, presynaptic release of DA (Gioanni et al, 1998;Mathé et al, 1996;Auclair et al, 2002), and/or potentiation of postsynaptic dopaminergic signaling (Eshel et al, 1990). However, DA-independent effects may also be involved since many a 1 -receptors are located on motorneurons downstream of dopaminergic neurons (Hou et al, 2002) and also on or near serotonergic and noradrenergic neurons (Morin et al, 1996).…”
Section: Role Of a 1 -Adrenoceptors In Behavioral Activitymentioning
confidence: 99%